A Meta-Analysis on the Risk Factors of Low Back Pain in Health Workers - Akbar, Muh. Syaiful; Rahardjo, Setyo Sri; Indarto, Dono (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2020)
Background: Low back pain is a common prob